Investigating the bacterial community of gray mangroves (Avicennia marina) in coastal areas of Tabuk region - Ghabban,Hanaa; Albalawi,Doha A.; Al-otaibi,Amenah S.; Alshehri,Dikhnah; Alenzi,Asma Massad; Alatawy,Marfat; Alatawi,Hanan Ali; Alnagar,Dalia Kamal; Bahieldin,Ahmad (PeerJ, 2024)
Mangrove vegetation, a threatened and unique inter-tidal ecosystem, harbours a complex and largely unexplored bacterial community crucial for nutrient cycling and the degradation of toxic pollutants in coastal areas. Despite its importance, the bacterial community composition of the gray mangrove (Avicennia marina) in the Red Sea coastal regions remains under-studied. This study aims to elucidate the structural and functional diversity of the microbiome in the bulk and rhizospheric soils associated with A. marina in the coastal areas of Ras Alshabaan-Umluj (Umluj) and Almunibrah-Al-Wajh (Al-Wajh) within the Tabuk region of Saudi Arabia. Amplicon sequencing targeting the 16S rRNA was performed using the metagenomic DNAs from the bulk and rhizospheric soil samples from Umluj and Al-Wajh. A total of 6,876 OTUs were recovered from all samples, of which 1,857 OTUs were common to all locations while the total number of OTUs unique to Al-wajh was higher (3,011 OTUs) than the total number of OTUs observed (1,324 OTUs) at Umluj site. Based on diversity indices, overall bacterial diversity was comparatively higher in rhizospheric soil samples of both sites. Comparing the diversity indices for the rhizosphere samples from the two sites revealed that the diversity was much higher in the rhizosphere samples from Al-Wajh as compared to those from Umluj. The most dominant genera in rhizosphere sample of Al-Wajh were Geminicoccus and Thermodesulfovibrio while the same habitat of the Umluj site was dominated by Propionibacterium, Corynebacterium and Staphylococcus. Bacterial functional potential prediction analyses showed that bacteria from two locations have almost similar patterns of functional genes including amino acids and carbohydrates metabolisms, sulfate reduction and C-1 compound metabolism and xenobiotics biodegradation. However, the rhizosphere samples of both sites harbour more genes involved in the utilization and assimilation of C-1 compounds. Our results reveal that bacterial communities inhabiting the rhizosphere of A. marina differed significantly from those in the bulk soil, suggesting a possible role of A. marina roots in shaping these bacterial communities. Additionally, not only vegetation but also geographical location appears to influence the overall bacterial composition at the two sites.
Keywords: Mangroves; Tabuk region; Avicennia marina; Microbiome; Soil; Bacterial diversity; Red sea; 16S rRNA